Systematic Literature Review: Analisis Implementasi Manajemen Risiko TI Menggunakan Framework COBIT di Sektor Industri Jasa - Nisa', Fathimatus Zahrotun; Febrianti, Ganes Dwi; Ajrina, Navy Nurlyn (Bulletin of Computer Science Research, 2023)
The use of Information Technology (IT) is an important part of all business activities, especially in the service sector. It is important to ensure the security, availability and integrity of their systems. The impact of failure in IT Risk Management greatly influences success. The implementation of IT Risk Management is needed to be able to help companies in the event of losses. In its use, a framework is needed that functions to identify, evaluate and manage existing risks. Therefore, this research will show the COBIT framework that is suitable for managing existing risk management. This research was carried out using the Systematic Literature Review method which started from the stages of formulating research questions, literature search, literature selection, data extraction and discussion aimed at answering Research Questions. In this research, 25 articles were found which were used as literature sources. The research results show that COBIT 2019 is the version of COBIT most often used in IT Risk Management in the industrial service sectors. In implementing COBIT, companies face various challenges such as lack of in-depth understanding of COBIT, lack of work process documentation and lack of operational standards for risk control and incompatibility of IT strategy with company strategy. This research also found that there are 8 points of COBIT implementation strategy to help service industry companies achieve organizational goals more effectively and efficiently through IT risk management.